Characteristics and immune checkpoint inhibitor effects on non-smoking non-small cell lung cancer with KRAS mutation: A single center cohort (STROBE-compliant). Issue 24 (17th June 2022) - Wu, Jia-Jun; Lee, Po-Hsin; Zheng, Zhe-Rong; Huang, Yen-Hsiang; Tseng, Jeng-Sen; Hsu, Kuo-Hsuan; Yang, Tsung-Ying; Yu, Sung-Liang; Chen, Kun-Chieh; Chang, Gee-Chen
Abstract : Abstract: Kirsten rat sarcoma ( KRAS ) mutation ( KRASm ) is associated with poor prognosis in non-small cell lung cancer (NSCLC) patients. We have aimed to survey NSCLC patients harboring KRASm in Taiwan, where never-smoking lung adenocarcinoma predominates, and analyze the immune checkpoint inhibitor effect on NSCLC harboring KRASm . NSCLC patients with KRASm were enrolled and tested on programmed death-ligand 1 (PD-L1) expression using available tissue. We analyzed their clinical features, PD-L1 status, responses to ICIs, and overall survival (OS). We studied 93 patients with a median age 66.0 years, 23.7% of whom were women, and 22.6% were never-smokers. The results showed that G12C (36.6%) was the most common KRASm . In 47 patients with available tissue for PD-L1 testing, PD-L1 expression was positive in 66.0% of patients, while PD-L1 ≥50% was higher in ever-smokers ( P  = .038). Among 23 patients receiving ICI treatment, those with PD-L1 ≥50% experience a 45.5% response rate to ICI. There were benefits from ICI treatment on OS compared with no ICI treatment (median OS 35.6 vs 9.8 months, P  = .002) for all of our patients, and for patients with PD-L1 ≥50% (median OS not-reached vs 8.4 months, P  = .008). There were no differences in survival across different KRAS subtypes ( P  = .666). Never-smokers composed more than one-fifth of KRASm in NSCLC in Taiwan. A high PD-L1 expression was related to smoking history and responded well to ICI. ICI treatment improved the OS in NSCLC patients with KRASm, particularly those with PD-L1 ≥50%.